Water supply and utilization in Johannesburg, 1886-1905 - Cosser, Elaine Margaret (My University, 2015)
This dissertation demonstrates that supply and non-supply of water significantly affected Johannesburg's early development. The introductory chapter examines the singularity of Johannesburg with regard to water sources, and the dearth of material addressing this subject. The second chapter considers the rapid transition from an ad hoc to a formal privatized water supply system in the context of the political and economic climate of the Transvaal; the discussion centres on the profiteering of water companies and the concomitant inadequacy of supply, which had a detrimental effect on industry and health. The third chapter depicts the emergence of local government and its attempts to improve the water supply, demonstrating that the powerlessness of the local state enabled an inferior supply to persist. An examination of the British authority's structural reorganization of municipal and water affairs in the wake of the Tueede Vryhejdsoorlog, and the limited effectiveness of these measures owing to the dilapidation of the supply system concludes the argument.